Research methods and thesis writing - Calmorin, Laurentina Palmer; Calmorin, Melchor A. (Manila, 2007)
This book, Methods of Research and Thesis Writing, endeavors to train students to become good researchers, having been prepared in response to the urgent need of the undergraduate ang graduate students who are writing research papers, theses, ot dissertations. This book may be used in any field of study, be it in education, psychology, sociology, biology, chemistry,physics, mathematics, statistics, economics, home economics, aquaculture, agriculture, fish processing technology, health, nursing, food and nutrition and many others... -- Preface
Keywords: Research methods